Real-world analysis of leuprorelin acetate microspheres-based neoadjuvant therapy for patients with high-risk prostate cancer - Fu, Changde; Xin, Jun; Lai, Jinjin; Zeng, Xu; Wang, Yongnan; Zhang, Wei (Frontiers in Oncology, 2025)
ObjectiveBoennuokang® leuprorelin acetate microspheres show a certain efficacy in patients with prostate cancer, but its utilization as neoadjuvant therapy in patients with high-risk prostate cancer remains unclear. Hence, this real-world study investigated the efficacy and safety of Boennuokang® leuprorelin acetate microspheres-based treatment as neoadjuvant therapy in patients with high-risk prostate cancer.MethodsThis retrospective study included 53 patients with high-risk prostate cancer who received Boennuokang® leuprorelin acetate microspheres as neoadjuvant therapy and laparoscopic radical prostatectomy.ResultsThe median prostate-specific antigen (PSA) was 34.1 ng/mL before neoadjuvant therapy and reduced to 0.8 ng/mL after neoadjuvant therapy (P<0.001). Testosterone showed a decreased tendency after neoadjuvant therapy, but without statistical significance (P=0.185). After surgery, 36 (67.9%) patients had negative surgical margin. The median (interquartile range) prostate volume reduced from 40.5 (33.4-55.2) mL before neoadjuvant therapy to 30.2 (25.2-40.2) mL after neoadjuvant therapy (P<0.001). Meanwhile, alkaline phosphatase before neoadjuvant therapy, at one month (M1), 3 months (M3), 6 months (M6), and 12 months (M12) after surgery tended to be increased (P=0.029), but this increment lacks clinical significance, while the glomerular filtration rate (P=0.441) and albumin (P=0.548) did not vary among different time points. Erectile dysfunction and loss of libido was the most common adverse event, with incidences of 84.9% during neoadjuvant therapy, 79.2% at M1, 71.7% at M3, 67.9% at M6, and 56.6% at M12.ConclusionBoennuokang® leuprorelin acetate microspheres-based treatment as neoadjuvant therapy decreases PSA, testosterone, and prostate volume, with acceptable positive surgical margin rate in patients with high-risk prostate cancer and its safety profiles should be validated.